Neighbourhood Social Control and Police Legitimacy: An Empirical and Theoretical Exploration in the Context of Contemporary Urban China - Wu, Guangzhen (The British journal of criminology, 2025)
Using data collected from a survey of 2,245 residents in a Chinese city, this study examined the influences of all three forms of social control processes (collective efficacy, semi-formal/public control and formal/public control) on police legitimacy. The results revealed a salient relationship between people’s assessment of these forms of neighbourhood social control and their police legitimacy judgements. This study also demonstrated a moderating role of perceived semi-public control, the most distinctive feature of social control in the Chinese social context, on the relationship between perceived public control and police legitimacy, further highlighting the importance of considering all potential forms of perceived neighbourhood social control to develop a theoretical understanding of perceptions of neighbourhood context and police legitimacy.